An Acta Orthopaedica educational article : Treatment of pediatric spondylolysis and spondylolisthesis - Helenius, Ilkka; Virkki, Ella; Toomela, Taavi; Studer, Daniel; Gehrchen, Martin; Ahonen, Matti (MJS Publishing, Medical Journals Sweden AB, 2025)
Spondylolysis is defined as a defect or elon-gation in the pars interarticularis of the lumbar spine, either unilateral or bilateral. Growing children with bilateral spon-dylolysis may develop spondylolisthesis, i.e., forward slip-ping of the affected vertebra. The etiology of spondyloly-sis is regarded as a stress fracture due to repetitive loading associated with a genetic predisposition. Lumbar magnetic resonance imaging (MRI) shows an increased signal intensity before an actual fracture line develops. In low grade spondy-lolisthesis, two-thirds of children with acute pediatric spondy-lolysis will undergo bony union with early activity restriction. Health-related quality of life is improved in patients achiev-ing bony union as compared with patients having non-union, of which one-fourth will additionally develop spondylolisthe-sis. In patients with high-grade spondylolisthesis, defined as a more than 50% forward slippage of the affected vertebra, spinal fusion is recommended to prevent further progression.